On the Benefits of Deforestation - a Quantitative Analysis (EXCERPT) - Gruner, Stefan (TECTUM, 2014)
After the Dipl.-Thesis had been accepted (by the Universiteit van Amsterdam, NL) in the year 1995, the work was published photographically as Micro-Fiche (for libraries) in the year 1997 by the German publisher TECTUM, whereby Stefan Gruner kept the copyright. In the meantime, those Micro-Fiches by TECTUM are no longer available, and also the original LaTeX source files have been lost. For these reasons - mainly out of historic interests - I am making my old work from the year 1995 available again (as an excerpt - not including every page) here via "UPSpace". It is also planned to carry out some replication case studies on the basis of those old experiments, to see if the results can be re-confirmed in the context of contemporary programming languages and programming environments. The excerpt available here via "UPSpace" contains all the technical details needed for the design of such replication experiments. Unfortunately the software itself, as it is described in the document, has also been lost after all those years.